2009
DOI: 10.1007/s10529-009-9930-7
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral transduction of hTGF-β1 enhances the chondrogenesis of bone marrow derived stromal cells

Abstract: TGF-beta1 plays a necessary and important role in the induction of chondrogenic differentiation of bone marrow stromal cells (BMSCs). In this study, porcine BMSCs were infected with a replication-deficient adenovirus expression vector carrying the hTGF-beta1 gene. The transduced BMSCs were cultured as pelleted micromasses in vitro for 21 days, seeded onto disk-shaped PGA scaffolds for 3 days and subsequently implanted into the subcutaneous tissue of mice. BMSCs transduced with AdhTGF-beta1 expressed and secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
(18 reference statements)
2
10
0
Order By: Relevance
“…Our data also confirmed that Standard‐hASCs remained sensitive to TGFβ1 signaling and that further addition of hrTGFβ1 increased the commitment into osteoblast, chondroblast, and VSMC lineages at the expense of adipogenesis. The role of TGFβ1 in osteoblast, chondroblast, and VSMC lineages was previously evaluated in different cell models . Our data confirmed TGFβ1 as a major factor with broad influence on the fate of primary hASCs in their plasticity.…”
Section: Discussionsupporting
confidence: 78%
“…Our data also confirmed that Standard‐hASCs remained sensitive to TGFβ1 signaling and that further addition of hrTGFβ1 increased the commitment into osteoblast, chondroblast, and VSMC lineages at the expense of adipogenesis. The role of TGFβ1 in osteoblast, chondroblast, and VSMC lineages was previously evaluated in different cell models . Our data confirmed TGFβ1 as a major factor with broad influence on the fate of primary hASCs in their plasticity.…”
Section: Discussionsupporting
confidence: 78%
“…In vitro , overexpression of IGF-I alone in MSCs could not induce chondrogenic differentiation, but in concert with TGFβ1, or BMP2, induced greater chondrogenic tissue than either alone [97, 98] . This is in support of in vivo experiments where MSCs were transfected or transduced withTGFβ1 to form ectopic cartilage in pigs, or filling full-thickness articular cartilage defects in rabbits and rats [99101] . AdBMP2-induced cartilage repair was compared in adipose, BM and periosteal MSCs of rat cartilage lesions.…”
Section: Skeletal Disorderssupporting
confidence: 59%
“…More than 50 adenovirus serotypes are available for gene therapy and serotype 5 (Ad5) has been the mostly used in both in vitro and in vivo studies. Adenovirus is used to transfer GF genes (TGF-β, FGF-2, IGF-1, BMPs and Growth and differentiation factor 5, GDF-5) into cells [8,20,25,[40][41][42][43][44][45][46][47][48][49]. Genes, in encapsuled viral [24] vector, can be injected directly in vivo [50,51] or through decalcified cortical bone matrix (DCBM) as scaffold that contains the viral particles [52].…”
Section: Viral Vectormentioning
confidence: 99%
“…The combination of gene therapy and scaffolds seems to greatly enhance both the efficiency and duration of transfected genes, leading to systems able to promote bone, cartilage, and osteochondral regeneration [22,23,26]. Scaffolds can be natural such as DBM, gelatine, alginate, fibrinogen and collagen based [16-18, 21, 27, 46, 52, 62, 71, 73, 84], or synthetic such as polyglycolic acid (PGA), polylactic acid (PLA) and poly(lactic-co-glycolide) (PLGA) [14,42,54,[82][83][84] (Table 1). Besides favouring cell engineering within the scaffold, their design can be used as guide for the correct integration and directional localization of cells in the defect.…”
Section: Use Of Scaffold In Gene Therapy Proceduresmentioning
confidence: 99%